S-thanatin functionalized liposome potentially targeting on Klebsiella pneumoniae and its application in sepsis mouse model - Fan, Xiaobo; Fan, Juxiang; Wang, Xiyong; Wu, Pengpeng; Wu, Guoqiu (Frontiers in Pharmacology, 2015)
S-thanatin (Ts) was a short antimicrobial peptide with selective antibacterial activity. In this study, we aimed to design a drug carrier with specific bacterial targeting potential. The positively charged Ts was modified onto the liposome surface by linking Ts to the constituent lipids via a PEG linker. The benefits of this design were evaluated by preparing a series of liposomes and comparing their biological effects in vitro and in vivo. The particle size and Zeta potential of the constructed liposomes were measured with a Zetasizer Nano ZS system and a confocal laser scanning microscope (CLSM). The in vitro drug delivery potential was evaluated by measuring the cellular uptake of encapsulated levofloxacin using HPLC. Ts-linked liposome or its conjugates with quantum dots favored bacterial cells, and increased the bacterial uptake of levofloxacin. In antimicrobial assays, the Ts and levofloxacin combination showed a synergistic effect, and Ts-LPs-LEV exhibited excellent activity against the quality control stain Klebsiella pneumoniae ATCC 700603 and restored the susceptibility of multidrug-resistant K. pneumoniae clinical isolates to levofloxacin in vitro. Furthermore, Ts-LPs-LEV markedly reduced the lethality rate of the septic shock and resulted in rapid bacterial clearance in mouse models receiving clinical MDR isolates. These results suggest that the Ts-functionalized liposome may be a promising antibiotic delivery system for clinical infectious disorders caused by MDR bacteria, in particular the sepsis related diseases.